The Effect of Learning Cycle 5E with Animation Media at Student Activities and Learning Outcomes - Anna Juniar; Vioni Angel Prisilya Sihombing (Universitas Negeri Medan, 2024)
This study aims to determine the effect of application of Cycle 5E learning model with animation media at learner activities and learning results. The sample was taken by random sampling of 32 learners at experiment and control room. The research was carried out by providing pre-check, after which learning material by nonelectrolyte and electrolyte solutions were applied with the Cycle 5E learning model with animation media at experiment room and the Conventional model at control class, then the posttest. From statistic processing, the following results were obtained: the average activity of learners at the experiment room was 89.76 and the control room was 80.55 with > or 4.59>1.67. The average learning outcome of learners at the experiment room was 81.71 and the control room was 72.96 with > or 5.57>1.67. Correlation between learner activities and learning results of experiment room learners at the calculation rcount Retrieved rcount=0.583 While rtableat α=0.05 (N = 32) is 0.349. With an index determination of 0.33 with a percentage of 33%. This means that there is a correlation between learner activities and learner learning results learned by the Cycle 5E learning model with animation media at material by nonelectrolyte and electrolyte solutions.